2018
DOI: 10.18178/ijcea.2018.9.2.700
|View full text |Cite
|
Sign up to set email alerts
|

Water Injection Fracture Pressure and Fracture Propagation Investigating in Poorly Consolidated Sandstone

Abstract: Predictions of fracture initiation and propagation pressure are an essential prerequisite to determine reasonable injection pressure for poorly consolidated sandstone. Most models for hydraulic fracturing based on elasticity mechanics are not applicable for poorly consolidated rocks. The fluid-solid coupling model based on elastic theory of porous media for poorly consolidated sandstone is established to analyze fracturing modes and fracture initiation pressure by adopting the maximum tensile stress criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Zhang et al believed that high sand ratio, low displacement, and continuous slug sanding technology should be used to achieve end screenout [10]. Fan et al believed that high efficiency fracturing fluid induced fractures short and wide, and it can achieve the purpose of filling and sand control [11]. Li et al studied the critical sand production rate and sand production area of unconsolidated sandstone fracturing packing based on the fluid-solid coupling model [12].…”
Section: Prefacementioning
confidence: 99%
“…Zhang et al believed that high sand ratio, low displacement, and continuous slug sanding technology should be used to achieve end screenout [10]. Fan et al believed that high efficiency fracturing fluid induced fractures short and wide, and it can achieve the purpose of filling and sand control [11]. Li et al studied the critical sand production rate and sand production area of unconsolidated sandstone fracturing packing based on the fluid-solid coupling model [12].…”
Section: Prefacementioning
confidence: 99%
“…The SRT data often do not fit into a straight line and do not exhibit one clear change in slope, thus making it difficult to estimate the fracture pressure. It often becomes subjective and leads to more than one outcome when analyzed by different engineers, leading to erroneous results. Various past studies , indicated that interpretation of fracture pressures by conventional analysis from the SRT is often subjective.…”
Section: Introductionmentioning
confidence: 99%